PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) PADA PEMBELAJARAN SENI BUDAYA (TARI) DI SMP NEGERI 01 SUNGAI PENUH - Fitri Purnama Sari; Yuliasma (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
The low learning outcomes in Arts and Culture (Dance) in Class VIII C of SMP Negeri 01 Sungai Penuh are caused by the inappropriate application of cooperative learning models and low student activity and participation, resulting in average student scores not reaching the established Minimum Learning Objective Completion Criteria (KKTP) of 83. This study aims to describe the improvement in student learning outcomes after implementing the Think, Pair and Share (TPS) cooperative learning model. This research is a Classroom Action Research (CAR) with a qualitative approach. The subjects were 28 students in class VIII C. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data collection techniques used written tests (cognitive) consisting of 25 objective questions and 7 essay questions, observation of student activities (covering visual, oral, listening, mental, and emotional activities), and documentation. The results showed that the application of the TPS model could improve student learning outcomes. In Cycle I, the average score of students' written tests reached 79.14 with a completion percentage of 35.7% ("good" criteria). After improvements in Cycle II, the average score increased to 94.07 with a completion percentage of 86% ("very good" criteria). Student learning activities also increased dramatically, especially in visual activities indicators (from 29% to 87.17%) and emotional activities (from 11% to 87.28%). This study concludes that the application of the Think, Pair and Share (TPS) cooperative learning model is effective in improving student learning outcomes in Arts and Culture (Dance). It is recommended that teachers explore variations of this learning model and that future researchers apply it to different scopes of material.